Theories of childhood : an introduction to Dewey, Montessori, Erikson, Piaget, and Vygotsky - Mooney, Carol Garhart (St. Paul : Redleaf press, 2013)
"Examine the work of five groundbreaking education theorists: John Dewey, Maria Montessori, Erik Erikson, Jean Piaget, and Lev Vygotsky--in relation to early childhood. Theories of Childhood, Second Edition, provides a basic introduction to each theorist and explains the relationship of theory to practice and its impact on real children, teachers, and classrooms"--
Bibliografija nakon svakog poglavlja.
Keywords: obiteljska pedagogija -- djetinjstvo; formiranje ličnosti -- odrastanje; predškolska pedagogija -- odgoj; alternativne škole i pravci